COMPARATIVE STUDY BETWEEN DIFFERENT COLORS OF ELASTOMERIC CHAIN: AN IN VITRO STUDY - Cigognini, Géssica Zamboni; Markoski, Karoline; Karch, Matheus; Giovanetti, Marcos; da Silva, Simone Camargo (Revista Uningá, 2020)
This in vitro study aimed to measure the influence of colors on the force degradation of orthodontic power chain of the Morelli® brand, after stretched and submerged in artificial saliva. The values were obtained after immediate measurement (time zero), 0.5, 1 and 24 hours of immersion. Twenty samples were selected at random from each of the colors of elastomeric chain. Each sample, composed of 4 links, was initially pre-stretched, with two probes, until stress. The determination of the amount of stretch of the elastics for measurement corresponds to 50% of the value of the initial pre-stretch. After the initial reading, each sample was removed from the dynamometer with the aid of a clinical tweezers and then placed on a device (template with pins) developed to accommodate the rubber bands. The sets (device + samples) were immersed in artificial saliva at 37± 1 °C (hysteresis). In the time intervals 30 minutes, 1 hour and 24 hours. The samples at time zero showed significant differences (p <0.05) between colors, with greater variation for gray and lesser for black. All colors showed greater force degradation in the first hour.